Design Of Application Monitoring Material Inventory And Agricultural Equipment Recording At PT Perkebunan Nusantara XII Surabaya - Raisa Alifianoor; Pantjawati Sudarmaningtyas; Henry Bambang Setyawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Availabilty for materials and agricultural tools for the treatment of the commodity at PT Perkebunan Nusantara XII Surabaya must be maintened because it’s affect the quality of agricultural commodities and production. However, the availability for materials and agricultural tools still not maintened. This problem occurs because PTPN XII didn’t know details of use materials in each garden. Because the material and availability of agricultural equipment is not maintained, then the garden will always did request the purchase of material, whereas there is a material that has accumulated on other plantations. In addition, the PTPN XII did not have a material usage indicator so it does not know the requirement of minimum material in any garden. Application materials inventory monitoring and recording of agriculture tools built to overcome the problems that exist in PTPN XII. Application materials inventory monitoring and recording of farm tools built on the theory of inventory, monitoring and evaluation, and its indicators. The indicators for this application uses material usage indicators for fertilization and pest / disease. Application monitoring supplies and agricultural tools have passed the test and has been running well. So the application monitoring and recording material inventory agriculture tools will help resolve any problems.